EARLY CHILDHOOD SECOND LANGUAGE ACQUISITION 4-5 YEARS OLD IN GO-GREEN GLINTUNG VILLAGE MALANG CITY - Redin Surya Bagas Santoso; Nurchasanah Nurchasanah (Universitas Pamulang, 2023)
The process of language children is one of the important essences of speech tendesi which in fact focuses on conveying a communication / conversational goal. The child's language form is characterized by the acquisition of the mother tongue at the beginning of its formation. Judging from the other side besides the mother tongue, the scope of the environment greatly influences a child to expand the range of second language acquisition. The purpose in this study is oriented towards the results of the description of the form of early childhood second language division of 4-5 years old in Glintung Go Green Village, which includes the stages of obtaining the second child's language, the process of both children's languages, and the factors of obtaining the language of both children. This research method uses qualitative descriptive methods with a case study approach. The results showed that the process of obtaining the language of the two children consisted of (1) the structure of the sequence and stages of obtaining the second language, including (a) the sequence with two words and (b) the stages of sentences in the word arrangement, (2) the process of obtaining the second language, including (a) the distribution of guided languages and (b) the acquisition of natural languages, and (3) factors that affect the acquisition of the second language in early childhood in Glintung Go Green Village, Malang City, among others (a) age factors, among others (a) age factors, (b) environmental factors, and (c) first language factors.